ANALISIS PENERAPAN SISTEM E-FILING DALAM MENYAMPAIKAN SURAT PEMBERITAHUAN (SPT) WAJIB PAJAK ORANG PRIBADI (STUDI PADA KPP PRATAMA KENDARI) - Akib, Mulyati; Amdayani, Lia (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACT This research aims to know the difference between a taxpayer compliance in conveying SPT Annual PPh WPOP before and after the application of the system of e-filing on the KPP Pratama Kendari. In this study, the data sources used are primary and secondary data. The methods used in this research is a descriptive analysis to describe and explain the result of taxpayer compliance ratio for 3 years before and after implementing the e-filing system. Based on the results of the study it can be concluded that there is no difference between a taxpayer compliance reports annual PPh WPOP before and after the implementation of the e-filing system. This is attempted from the research results obtained the value of user contributions to e-filing tax until the year 2014 of only 3,94%, thus it can be said the implementation of the e-filing system has yet to give a positive effect against a compliance ratio of tax payers caused yet effective use of e-filing system so that it can not be a powerful solution to improve Taxpayer Compliance in conveying SPT Annual PPh WPOP in KPP Pratama Kendari. Keywords: e-filing System and Taxpayer Compliance